Analysis Control Of Inventory Of Non Subsidy Fertilizer Merchandise With Economic Order Quantity (EOQ) Method In CV. Dohar Agro Mandiri - Ferza Dwianda Afrimarsa; Neri Susanti; Tito Irwanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Economic Order Quantity (EOQ) is a mathematical model that determines the number of items that must be ordered to meet the projected demand, with minimized inventory costs. The types of costs to run the business cycle are storage costs and ordering costs. The purpose of this research is to analyze "Analysis of Non-Subsidized Fertilizer Inventory Control with Economic Order Quantity (EOQ) Method at CV. Dohar Agro Mandiri. The total inventory obtained using the EOQ method is 11,003 with a purchase frequency of 3 times. Using the EOQ method the company must reorder when the merchandise inventory is 1,015 zak, with the EOQ method the maximum inventory that the company must maintain is 12,018 per day. The total inventory cost of fertilizer merchandise inventory is 24,648. In other words, inventory control using the EOQ method can help companies achieve an optimal level of inventory ordering and ordering frequency.